IMPACT OF VITAMIN E AND SELENIUM INTAKE ON ANTIOXIDANT PROTECTION INDICATORS DURING PHYSICAL EXERTION IN INDIVIDUALS WITH HYPERTENSION - Iryna Dronyk; Roman Dutka; Nathalia Chmyr; Roman Pshyk; Oksana Didenko (Acta Medica Leopoliensia)
Hypertension remains one of the main problems in modern medicine since it is a pathogenetic factor leading to a large number of cardiovascular diseases and premature death.